Analysis of biomechanical differences based on distance changes in connection with approach swings of tour-professional golfers - You, M.-S.; Lee, K.-I. (Korean Journal of Sport Biomechanics, 2016)
Objective: This study aimed to compare differences in biomechanical factors according to distance changes in relation to approaches during a round of golf to obtain basic data on golf swings. Methods: The research subjects were 8 KPGA-affiliated professional golfers who performed approach shots that put a ball into a circle of 8 feet in diameter from distances of 30, 50, and 70 m. Data were collected by using six infrared cameras and a ground reaction force device, which were applied to calculate biomechanical factors by using Kwon3D XP. The calculated data were subjected to one-way ANOVA by using SPSS 20.0, with the significance level set at p value of 0.05. Results: Elapsed time, stance width, clubhead position variation, clubhead synthesis speed, and cocking angle significantly differed according to distance change during the approach swing. Clubhead speed was positively related with stance width and clubhead displacement. Ground reaction force significantly differed according to distance change during the approach swing. Factors before and after showed differences in other states, except in the impact state. Conclusion: In the present study, we drew several conclusions regarding biomechanical factors and ground reaction forces according to distance change in the approach swing of professional golfers. According to these conclusions, we suggest that distance control with swing range is more important than power control in maintaining the accuracy and consistency of golf swing and is the most important mechanism of golf swing.